Role of the Conjoined Tendon in Hip Stability Post-Total Hip Arthroplasty: Insights From a Direct Anterior Approach Cadaver Study - Gongyin Zhao, MD, PhD; Chenyu Zhao, MBBS; Hongwei Bao, MD; Junting Liu, MD; Baojun Zhou, MD; Yuji Wang, MD, PhD (Arthroplasty Today)
Background: Hip dislocation represents a significant complication encountered following hip arthroplasty procedures. In this investigation, we conducted a comparative analysis of the biomechanical characteristics exhibited by the piriformis and the conjoined tendon after total hip arthroplasty (THA) via the direct anterior approach (DAA), utilizing cadaveric specimens. The objective is to ascertain the relative significance of the piriformis muscle and the conjoined tendon in mitigating hip dislocation. Methods: A total of 16 hip joints from 8 freshly frozen cadavers were selected and stratified into 2 groups: the piriformis tendon (PT) group and the conjoined tendon (CT) group. Following THA via the DAA, measurements were taken to record the torque required to induce hip dislocation under various conditions. Torque readings were obtained with the tendon in its intact state (intact group) and after preservation or reconstruction of either the PT or the CT. Results: The torques of anterior and posterior dislocation in PT group were 22.24 ± 4.53 N.m and 30.7 ± 15.5 N.m following tendon severed, and 20.04 ± 2.67 N.m and 17.5 ± 6.7 N.m following reconstruction. There were no differences compared to the intact group. The torque decreased in the CT group after CT was severed with the torques dropping from 31.2 ± 7.6 N.m to 8.18 ± 2.6 N.m (P < .0001) for anterior dislocation, and from 34.9 ± 8.3 N.m to 9.8 ± 2.8 N.m (P < .0001) for posterior dislocation. Following reconstruction, the torque required for dislocation significantly increased (P < .0001). Conclusions: This study underscores the preeminent role of the CT in ensuring hip stability following THA via DAA, highlighting the cruciality of its preservation and reconstruction during surgical interventions.